Incidence and factors associated with immediate adverse neonatal outcomes among emergency obstetric referrals in labor at a tertiary hospital in Uganda: a prospective cohort study - Geoffrey Okot; Samuel Omara; Musa Kasujja; Francis Pebolo Pebalo; Petrus Baruti; Naranjo Almenares Ubarnel (BMC, 2024)
Abstract Background High rates of adverse neonatal outcomes in resource-limited settings are multifactorial, varying by country, region, and institution. In sub-Saharan Africa, the majority of adverse neonatal outcomes are intrapartum related, and studies in Uganda have shown that referral in labor is a major determinant of adverse neonatal outcomes. This study aimed to assess the incidence and factors associated with immediate adverse neonatal outcomes among emergency obstetric referrals in labor at a tertiary hospital in Eastern Uganda. Materials and methods This was a prospective cohort study involving 265 women who were referred in labor to Jinja Regional Referral Hospital in Uganda with emergency obstetric complications. The exposure of interest was being referred with obstetrical emergency, and the outcome variable was adverse neonatal outcomes. The study was conducted between July 5, 2023, and October 5, 2023. Consecutive sampling was used, and data on sociodemographic and obstetric factors, referral related factors, as well as the primary outcome variable (adverse neonatal outcome) were collected via interviewer-administered questionnaires. The data were then cleaned, coded, and analyzed using STATA version 14. Log-binomial regression determined risk ratios and associations for factors related to adverse neonatal outcomes. Variables with p-values < 0.2 in bivariable analysis were included in the multivariable analysis, where significance was set at p < 0.05. Results Of the 265 women exposed to emergency obstetrical referrals, 40% experienced adverse neonatal outcomes, a composite measure including neonatal intensive care admission (27.6%), low Apgar score (23.8%), fresh stillbirth (11.3%), early-onset neonatal infection (6.8%), and early neonatal death (2.3%). Factors significantly associated with adverse neonatal outcomes were; maternal age ≥ 35 years (aRR = 1.72, CI:1.194-2.477, p value = 0.004), APH (aRR = 2.48, CI: 1.859-3.311, p-value < 0.001), and non-reassuring fetal status (aRR = 1.90, CI: 1.394-2.584, p-value < 0.001). Conclusions The study found a high rate of adverse neonatal outcomes among emergency obstetric referrals, with 40% of participants facing issues like ICU admissions, low Apgar scores and fresh stillbirth. Key factors included maternal age over 35, antepartum hemorrhage, and non-reassuring fetal status. These results highlight the urgent need for targeted interventions in emergency obstetric care. Strategies should enhance referral systems, improve facility preparedness, train healthcare providers, and educate communities on timely referrals and managing high-risk pregnancies.